Developmental Changes in the Magnitude of Representational Momentum Among Nursery School Children: A Longitudinal Study - Mori, Shiro; Nakamoto, Hiroki; Shirai, Nobu; Imanaka, Kuniyasu (Frontiers in Psychology, 2022)
Representational momentum (RM) is a well-known phenomenon that occurs when a moving object vanishes suddenly and the memory of its final or vanishing position is displaced forward in the direction of its motion. Many studies have shown evidence of various perceptual and cognitive characteristics of RM in various daily aspects, sports, development, and aging. Here we examined the longitudinal developmental changes in the displacement magnitudes of RM among younger (5-year-old) and older (6-year-old) nursery school children for pointing and judging tasks. In our experiments, the children were asked to point at by their finger (pointing task) and judge the spatial location (judging task) of the vanishing point of a moving stimulus. Our results showed that the mean magnitudes of RM significantly decreased from 5- to 6-year-old children for the pointing and judging tasks, although the mean magnitude of RM was significantly greater in the 5-year-old children for the pointing task but not for the judging task. We further examined the developmental changes in RM for a wide range of ages based on data from the present study (5-year-old children) and our previous study (Shirai et al., 2018; 7- and 11-year-old children and 22-year-old adults). This ad hoc examination showed that the magnitude of RM was significantly greater in 5-year-old children than in adults for the pointing and judging tasks. Our findings suggest that the magnitude of RM was significantly greater in young children than in adults and significantly decreased in young children through adults for the pointing and judging tasks.